Hydrogeological and hydrogeochemical investigation of a Precambrian basement aquifer in Bugesera Region (Burundi) - Bakundukize, Charles (Afrika Focus, 2012)
This study clearly shows that Bugesera region has genuine groundwater potential which could be circumscribed and tapped in order to provide enough drinking water to the inhabitants of the area. Thus, this study recommends further investigations and measures, including, geophysical investigations coupled to reconnaissance drillings, the installation of a network of piezometers to monitor the groundwater level variation, measurement of the discharge rate and water level fluctuation in the complex of marshlands and lakes, monitoring of groundwater quality and further pumping tests in order to rfine the distribution of hydraulic parameters in the study area.